"Post-Roe" Abortion Policy Context Heightens the Imperative for Multilevel, Comprehensive, Integrated Health Education. (December 2022) - Rice, Whitney S.; Narasimhan, Subasri; Newton-Levinson, Anna; Pringle, Johanna; Redd, Sara K.; Evans, Dabney P.
The exceptionalism of abortion in public health education, due to social stigma, politicization, and lack of training, contributes to misinformation, policies unjustified by rigorous science, lack of access to person-centered health care, and systemic pregnancy-related inequities. Now that abortion access has vanished for large portions of the United States, following the Supreme Court decision in Dobbs v. Jackson Women's Health Organization ( JWHO ), health educators must work to eliminate abortion-related silos, destigmatize abortion education, and bring comprehensive sexual and reproductive health information and evidence to the many audiences that will require it. We discuss consequences of abortion exceptionalism in health education for the public, health care providers, pregnant people, and health professionals in training—and opportunities to better and more accessibly provide sexual and reproductive health education to these audiences.